Novel nonlinear FMCW radar for precise distance and velocity measurements - Vossiek, Martin; von Kerssenbrock, T.; Heide, Patric (IEEE MTT-S International Microwave Symposium, 1998)
A new nonlinear FMCW radar concept for precise distance and velocity measurements is presented. The radar system incorporates a surface acoustic wave (SAW) reference device used for an online detection of oscillator phase errors. With a specific Doppler/distance ambiguity function, that is continuously adapted to the measured phase error, the target signal is evaluated. By applying this novel technique the optimal distance resolution at a given sweep bandwidth is obtained independently of the Doppler resolution. The proposed system approach has been evaluated with a 77 GHz radar incorporating a flip-chip MMIC VCO.
UnivIS-Import:2015-04-16:Pub.1998.tech.IE.LEH.noveln